PELATIHAN MEDIA E-LEARNING BERBASIS WEB PADA GURU SDN JATIMEKAR I BEKASI - Nunu Kustian; Siti Julaeha; Dudi Parulian (Politeknik Negeri Sriwijaya, 2021)
The role of the teacher is very important in the success of students and the quality of education in schools, but many teachers only rely on one application so that teaching and learning activities are boring for students such as the use of smartphones that are not optimal by teachers and students and lack of knowledge of web based E-Learning media to support activities online student learning and evaluation. Quizizz is a web based E-Learning media that can be used by teachers in distance learning whose use is to create online exercises for students, providing maximum potential in technological literacy which is very useful in the current Covid 19 pandemic situation. The method used in training and mentoring teachers at SDN Jatimekar I Bekasi as an alternative application in carrying out daily asssessments and is easy to operate by the teacher, where the teacher can act as admin, examiner, or who makes questions independently. Quizizz has the potential for innovation in distance learning between teachers and students with mobile friendly features, which can be downloaded on the play store or google play which is already available on smartphones.